Disposición del docente universitario respecto a la evaluación de pares / Teachers’ perceptions of peer evaluation in a public university in Mexico - Ortega Ávila, Aurora Berenice (Revista Internacional de Aprendizaje en la Educación Superior, 2015)
ABSTRACT In order to judge the effectiveness of their programs, educational institutions measure performance of teachers students. In particular, the evaluation of teacher performance has become one of the most widely used methods for gauging the quality of teaching. In universities, the judgement of teacher effectiveness is based largely on the measurement of teacher performance. In order to accomplish real change in teacher effectiveness it is essential to create “…training programs/evaluation which accompany the teacher in their daily work.... it is about designing formative assessment programs”(Pacheco and Diaz ,2000 p.27). The purpose of formative evaluation programs is to help the teacher improve their practices over time and to encourage their participation in that process. In order to accomplish this, it is necessary to develop programs that support the teacher throughout the evaluation process. The intent of this paper is to explore the perceptions of teachers in the roles of evaluator and evaluated as they participate in an evaluation of their colleagues. With this it aims to promote a culture of evaluation where the teacher who is advised by his or her colleagues finds support in his or her teaching development. Peer review is considered an opportunity for professional growth and thereby improves the performance of teachers in the classroom. RESUMEN La presente investigación es de carácter cualitativo descriptivo y se enfoca al análisis de la de la evaluación de pares, desde la percepción de los docentes mexicanos en un contexto universitario. Para el estudio se formaron 5 díadas de profesores provenientes de las diferentes licenciaturas del campus. Cada uno de los profesores desempeñó los roles de observador y observado durante el proceso. La información fue recolectada a través de entrevistas. Entre los resultados obtenidos en esta investigación fue la percepción de la evaluación de pares como una buena práctica para mejorar tanto el desempeño profesional del docente, así como la calidad educativa de una institución. El estudio plantea la evaluación de pares como una gran experiencia de aprendizaje. La fase de retroalimentación entre los profesores resultó ser crucial en este proceso de evaluación de pares. Entre las recomendaciones se sugiere implantar una metodología y técnicas que permitan crear un ambiente de confianza y credibilidad. Finalmente como resultado del análisis de esta investigación se ofrece una serie de lineamientos para implementar el proceso de evaluación de pares. Contacto principal: bereniceortega@gmail.com